2022
DOI: 10.1021/acsami.1c24336
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom-Substituted P2–Na2/3Ni1/4Mg1/12Mn2/3O2 Cathode with {010} Exposing Facets Boost Anionic Activity and High-Rate Performance for Na-Ion Batteries

Abstract: As an attractive cathode candidate for sodium-ion batteries, P2-type Na 2/3 Ni 1/3 Mn 2/3 O 2 is famous for its high stability in humid air, attractive capacity, and high operating voltage. However, the low Na + transport kinetics, oxygen-redox reactions, and irreversible structural evolution at high-voltage areas hinder its practical application. Herein, a comprehensive study of a microbar P2-type Ni 2/3 Ni 1/4 Mg 1/12 Mn 2/3 O 2 material with {010} facets is presented, which exhibits high reversibility of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
(89 reference statements)
3
26
0
Order By: Relevance
“…It has been reported that ethanol molecules in the solvent have a lower adsorption energy on the {001} facet than on the {010} facet of the precursor, leading to the preferential growth of the {010} facet and the formation of the one-dimensional microrod structure. 39 Thereby, the fully exposed {010} facet provides sufficient channels for the transport of Na + , leading to improved rate performance of the cathodes. 40,41 As for the hollow structure observed in the TEM image (Figure 1e), it is probably attributed to the release of CO 2 during the hightemperature calcination process.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ethanol molecules in the solvent have a lower adsorption energy on the {001} facet than on the {010} facet of the precursor, leading to the preferential growth of the {010} facet and the formation of the one-dimensional microrod structure. 39 Thereby, the fully exposed {010} facet provides sufficient channels for the transport of Na + , leading to improved rate performance of the cathodes. 40,41 As for the hollow structure observed in the TEM image (Figure 1e), it is probably attributed to the release of CO 2 during the hightemperature calcination process.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3d, the volume change rate of LMNM is at a much lower level (0.49%) compared to the Ni-Mn cathode materials reported in the literature. [15,17,31,32,[42][43][44][45] As a sharp contrast, we also performed in situ XRD characterization of NM (Figure S7, Supporting Information). The results show that the characteristic peak of O2 phase starts to appear in NM material when it is charged to 4.2 V. The calculated volume change of the phase change fraction reaches 22.2%.…”
Section: Mechanism Of Structural Evolutionmentioning
confidence: 99%
“…The unsustainable consumption of fossil fuels accelerates energy transition to renewable energy such as wind energy and solar energy. , However, achieving efficient utilization of these clean energy sources requires large-scale energy storage devices. , Due to the abundant sodium resources and low cost, Na-ion batteries (NIBs) are considered as one of the most promising candidate materials for low-cost and large-scale energy storage. …”
Section: Introductionmentioning
confidence: 99%